Radical democratic citizenship at work in an adverse economic environment: the case of workers' co-operatives in Scotland. Issue 1 (2nd January 2022) - Zaunseder, Andreas
ABSTRACT: Worker co-operatives generally embrace democracy in their ownership and decision-making structure. However, the commitment to a flat organisational hierarchy, implementation of equal wage policy, and the pursuit of a strong ethical policy position these co-operatives on the highly principled side of the co-operative landscape in the UK. This paper draws on an ethnographic study of five such principled workers' co-operatives operating in a most adverse economic context, the UK capitalist market economy. The study explores collective decision-making and the personal investment as two important political aspects. Workplace democracy and the personal are interlinked paradigms for political praxis – as practiced democracy, immanent critique of the hegemonic corporate way of organising work, as well as prefiguring a viable alternative. Taking the perspective of radical worker co-operatives, this article caters to an urgently needed conceptualisation of radical democratic citizenship at work.